Analysis of barriers and prerequisites for the circular economy implementation in Ukraine (Economics and region, 2025)
The article examines the contemporary issue of transforming the traditional linear economic model in the context of global environmental challenges and the depletion of natural resources. The main focus is on identifying key obstacles that hinder the implementation of the circular economy in Ukraine, including regulatory inconsistencies, insufficient government support, high investment costs in "green" technologies, and low environmental awareness among both businesses and consumers. The article is based on a systematic analysis of the theoretical foundations of the circular economy, including concepts of sustainable development, industrial ecology, and closed-loop economy, as well as an analysis of global experience, particularly cases from the European Union, the Netherlands, Sweden, Germany, and China. The conducted study allows for the identification of structural barriers and the determination of prerequisites that ensure the effective integration of the circular model into the national economy. The methodological basis of the study is a comparative analysis of the regulatory framework, state policies, technological infrastructure, and sociocultural factors influencing the implementation of the circular economy. The analysis of scientific sources, publications by foreign and domestic scholars, as well as strategic documents, confirms the need for a comprehensive approach that includes the development of financial incentives, legislative reform, support for innovative technologies, and the formation of environmental culture. The obtained results allow for the formulation of policy recommendations aimed at harmonizing national legislation with European standards, creating effective mechanisms for financing environmental initiatives, and developing educational programs to enhance environmental awareness. The scientific value of the study lies in the comprehensive analysis of multidimensional barriers to the implementation of the circular economy, which makes it possible to propose an integrated model for transitioning to sustainable development. The findings presented in the article can serve as a basis for further scientific research and the development of practical measures to stimulate the circular transformation of Ukraine’s economy.
Keywords: circular economy; sustainable development; environmental innovations; public policy; resource management; waste recycling; financial incentives; environmental awareness